(untitled) (Journal of the College of Basic Education, 2022)
The current research deals with (the visual discourse of the art of sculpture between metaphor and innovation) a comparative study between the works of sculptors Umberto Jacomti and Henry Moore. The research, where the second chapter included four sections, the first of which dealt with the metaphor, its types, the mechanism of its employment and its preoccupations, and the second section dealt with innovation as a concept, as well as the visual discourse between the formal transformer and innovation. By searching the results, which belong to the sculptors.